Pretreatment Dynamic Susceptibility Contrast MRI Perfusion in Glioblastoma: Prediction of EGFR Gene Amplification - Gupta, A.; Young, R. J.; Shah, A. D.; Schweitzer, A. D.; Graber, J. J.; Shi, W.; Zhang, Z.; Huse, J.; Omuro, A. M. P. (Clinical neuroradiology (Munich), 2015)
Background and Purpose Molecular and genetic testing is becoming increasingly relevant in GBM. We sought to determine whether dynamic susceptibility contrast (DSC) magnetic resonance imaging (MRI) perfusion imaging could predict EGFR-defined subtypes of GBM. Materials and Methods We retrospectively identified 106 consecutive glioblastoma (GBM) patients with known EGFR gene amplification, and a subset of 65 patients who also had known EGFRvIII gene mutation status. All patients underwent T2* DSC MRI perfusion. DSC perfusion maps and T2* signal intensity time curves were evaluated, and the following measures of tumor perfusion were recorded: (1) maximum relative cerebral blood volume (rCBV), (2) relative peak height (rPH), and (3) percent signal recovery (PSR). The imaging metrics were correlated to EGFR gene amplification and EGFRvIII mutation status using univariate analyses. Results EGFR amplification was present in 44 (41.5 %) subjects and absent in 62 (58.5 %). Among the 65 subjects who had undergone EGFRvIII mutation transcript analysis, 18 subjects (27.7 %) tested positive for the EGFRvIII mutation, whereas 47 (72.3 %) did not. Higher median rCBV (3.31 versus 2.62, p = 0.01) and lower PSR (0.70 versus 0.78, p = 0.03) were associated with high levels of EGFR amplification. Higher median rPH (3.68 versus 2.76, p = 0.03) was associated with EGFRvIII mutation. Conclusion DSC MRI perfusion may have a role in identifying patients with EGFR gene amplification and EGFRvIII gene mutation status, potential targets for individualized treatment protocols. Our results raise the need for further investigation for imaging biomarkers of genetically unique GBM subtypes.